High-Resolution Analysis of Temporal Variation and Driving Factors of CO2 Concentration in Nanning City in Spring 2024 - Jinghang Feng; Xuemei Chen; Huilin Liu; Zhaoyu Mo; Shiyang Yan; Xiaoyu Peng; Hongjiao Li; Hao Li; Hui Liao; Jiahui Lu (Atmosphere)
In this study, based on high-resolution online monitoring data of CO2 concentration in Nanning City in the spring of 2024, we analyzed the characteristics of diurnal and monthly changes of CO2 concentration in Nanning City and explored the influencing factors through the background sieving method and Lagrangian Particle Dispersion Model (LPDM) traceability simulations combined with meteorological factor analysis. The results demonstrates that the diurnal variation of CO2 concentration in Nanning City exhibits a bimodal pattern of peak in the afternoon and trough in the early morning, with a mean concentration of 460 ± 15 ppm. Transportation emissions were identified as the dominant source of this variation. The trend of monthly concentration changes was first increasing and then decreasing, with an increase in February–March and a decrease in April, indicating that it was affected by the combined effect of vegetation photosynthesis and urban human activities. The results of the background sieving method and traceability simulation analysis showed that the CO2 concentration in Nanning City was more affected by local emission sources than sinks, and the industrial sources and transportation sources in the north–south direction had a significant effect on the CO2 concentration. This research provides critical data support for formulating carbon reduction strategies and coordinated atmospheric environment management in subtropical cities.